Successful TCRαβ/CD19-Depleted Hematopoietic Cell Transplantation for a Patient With Artemis Deficiency. Issue 2 (6th March 2023) - Tomomasa, Dan; Isoda, Takeshi; Mitsuiki, Noriko; Inoue, Kento; Nishimura, Akira; Uda, Kazuhiro; Uchiyama, Toru; Yamashita, Motoi; Kamiya, Takahiro; Endo, Akifumi; Takagi, Masatoshi; Imai, Kohsuke; et al.
Abstract : Artemis deficiency is characterized by DNA double-strand breaks repairing dysfunction and increased sensitivity to ionizing radiation and alkylating reagents. We describe the first successful case of T-cell receptor [TCR]αβ/CD19-depleted hematopoietic cell transplantation [HCT] for Artemis deficiency in Japan. A 6-month-old Korean boy was diagnosed with Artemis-deficient severe combined immunodeficiency. He had no human leukocyte antigen (HLA)-matched sibling or unrelated donor. Therefore, TCRαβ/CD19-depleted HCT from his haploidentical mother was performed. Despite mixed chimerism in whole blood, T cells achieved complete donor chimerism 6 months after HCT. TCRαβ/CD19-depleted HCT could be an effective treatment for patients with radiation-sensitive severe combined immunodeficiency.